Violências e gênero no cotidiano escolar : estudo de caso em uma escola da rede pública estadual sergipana - Couto, Maria Aparecida Souza (2008)
This work was to unveil main goal, in terms of gender, the expression of violence in the daily school, with special emphasis on the optical of teachers, the implications/barriers in the construction of identity, gender and citizenship full of students of the state schools. The qualitative research-type case study of ethnographic stamp allowed deepen knowledge of the phenomenon of violence and the construction of identity through instruments such as a review of relevant literature, statistics offered by institutions of research, participant observation and semi-structured interview conducted with teachers, students and technical team of Alexandria School, located in the municipality of Nossa Senhora do Socorro-SE. It is to understand violence as behavior learned in the process of socialization, cultural construction, entered into historical periods in which the human act sets itself according to a social, economic and political force, being linked to moral codes and groups that to use to stay in power and the constraints racial, ethnic, gender and class. It was observed that the violence in/inside the school as well as in school are interrelated and present in the daily school students reaching indistinctly, staff and faculty. The violence are espraiadas in the daily school, it appears his ascenção among girls who use violence as verbal and symbolic expressions of violence while boys use up more of the physical and symbolic violence. The school is not planned to speak so systematized in the face of frequent incidents of violence in the relations of gender. It adopts postures individualized deny that the confrontation with the challenges that the school should tackle contemporary modern failing to deny the development of Just identities of gender and citizenship full of students. The approach of violence in school and gender as a category of analysis, is a possibility for expansion and understanding of the phenomenon with a view to their confrontation.